Stress Analysis on Water Injection Turbine Meter Blades - Muhammad Taufiq bin Tajuddin, Muhammad Taufiq (Universiti Teknologi Petronas, 2010)
The objectives of this project is to analyse how stress acts on the water injection turbine meter blades and study whether the high pressure difference is the cause of the bent turbine blades. Water Injection Turbine Meters are used to measure the volume of water injection that is being injected to the reservoir. However the main problem of the turbine meter is that the blades are easily bent. This is due to the high pressure difference in the water injection pipeline during water injection back online. A pressure of 8000 kpag will be acted towards the blade and in a long run, the blade will be bent due to this. The analysis of stress values that are produced are the key factor of the project. 430 Stainless Steel will be used as the material of the Turbine Blade in this project. The turbine blades will be designed in CATIA. The design will be based on one of an existing liquid turbine meter. Then it will be meshed and exported to ANSYS where the stress analysis will be done. The pressure distribution of the NACA 4415 airfoil will be used to assume that it has the same pressure distribution with the turbine blades.In conclusion, this analysis would be helpful since with the results from this project, a new design could be created to solve the problem of the bent turbine blades. This will benefit the Oil and Gas Company in the long run since the turbine meters will last longer.